Terrorism - Outman, James L., 1946-; Outman, Elisabeth M., 1951-; May, Matthew; Sawinski, Diane M. (Detroit : U.X.L, 2003)
Profiles twenty-six individuals who participated in the story and history of terrorism.
volume 1. Almanac - volume 2. Biographies - volume 3. Primary sources volume 4. Reference library cumulative index
Includes bibliographical references and index
Keywords: Terrorism; Terrorists -- Biography; Terrorists